Dental injuries in ice hockey games and training - Lahti, H.; Sane, J.; Ylipaavalniemi, P. (Medicine & Science in Sports & Exercise, 2002)
PURPOSE: The purpose of this study was to determine the incidence, cause, and nature of maxillofacial and dental injuries in ice hockey games and training and also evaluate the use and the effect of dental or facial guards. METHODS: Maxillofacial and dental ice hockey injuries in Finland were studied during years 1991 and 1992. Material was gathered from the insurance company that had practically all the ice hockey licenses in those years. The material consisted of 479 injured ice hockey players who suffered from 650 separate injuries. The most common dental injury was a noncomplicated crown fracture, which accounted for 43.5% of all maxillofacial or dental injuries. Of these noncomplicated crown fractures, almost 70% occurred in the games. RESULTS: The most common cause of accidents was a blow from the ice hockey stick. The stick as a cause of injury was approximately 3 times as common in the games than in training. Only 10% of injured players wore some kind of protective guard. CONCLUSION: A mandatory use of mouthguards and face masks or tightened rules for protection to decrease the high number of maxillofacial and dental injuries in the ice hockey games should be considered.